Konservasi dan Kondisi Terumbu Karang di Kampung Saporkren Distrik Waigeo Selatan, Kabupaten Raja Ampat, Papua Barat - Marthen L.R. Bartholomeus; Dirk Y.P. Runtuboi; Rosye H.R. Tanjung (Jurnal Biologi Papua, 2013)
Conservation effort and knowledge on coral reef ecosystem are necessary to protect marine ecosystem. Coral reef ecosystem is very important to support marine biota especially fishes and benthos. The presence of coral reef indirectly support local people income, therefore is is necessary to conserve coral reef ecosystem. District of South Waigeo is one of tourist area as well as preserve area in Raja Ampat Regency of Papua Barat Province. The aim of this study is to identify the current condition of coral reef in Saporken Village of South waigeo District. Data were collected by survey method using coral reefs Point intercept transect method, observation and interviews to determine the social, economic and cultural impact., and measures taken to manage coral reef management in village Saporkren Marine Protected Areas. The results showed that knowledge Saporkren Village community, the conservation community knows about how destructive such arrests are not carried out the bombing, while the traditional way people work is local wisdom. Condition of coral cover in the village of Marine Protected Areas Saporkren in good condition (live coral cover=51%) and very good water quality, flow velocity at high tide ranged from 4.25 to 22.3 cm/sec and the flow velocity at low tide over small ranging from 5.07 to 19.60 cm/sec, salinity ranged from 32–35‰ and wave height ranged from 0.75 m. Based on the results of this study concluded that: Village community know Saporkren conservation activities of local government programs, and the traditional way to preserve coral reef still implemented.Key words: Conservation, coral reefs, Saporkren village, Raja Ampat.